Indeterminacy tolerance as a basis of hemispheric asymmetry within prefrontal cortex - Goel, Vinod (Frontiers in Human Neuroscience, 2015)
There is an important hemispheric distinction in the functional organization of prefrontal cortex (PFC) that has not been fully recognized and explored. Research with split-brain patients provides considerable evidence for a left hemisphere “interpreter” that abhors indeterminacy and automatically draws inferences to complete patterns (real or imaginary). It is suggested that this “interpreter” function may be a byproduct of the linguistic capabilities of the left hemisphere. This same literature initially limited the role of the right hemisphere to little more than visual organization. Recent reviews have garnered evidence for several different roles for the right prefrontal cortex in reasoning, problem solving, and decision-making. We here focus on the beneficial but neglected role of indeterminacy in real-world problem solving and argue that the right PFC complements the left PFC “interpreter” by maintaining, and even enhancing indeterminacy. Successful real-world functioning is a delicate balancing act between these two systems.